2019
DOI: 10.1155/2019/4362539
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Interhemispheric Functional Organization in Children with Dyskinetic Cerebral Palsy

Abstract: Background. Hemispheric asymmetry is one fundamental principle of neuronal organization. Interhemispheric connectivity and lateralization of intrinsic networks in the resting-state brain demonstrate the interhemispheric functional organization and can be affected by disease processes. This study aims to investigate the interhemispheric organization in children with dyskinetic cerebral palsy (DCP) based on resting-state functional MRI (fMRI). Methods. 24 children with DCP and 20 healthy children were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 42 publications
(52 reference statements)
1
41
0
Order By: Relevance
“…194 A multimodal study in PVI suggested that differences in inter-and intrahemispheric functional connectivity may be CST-wiring specific. 194 Seed-based analyses have indicated that AISs have significantly lower interhemispheric functional connectivity values in sensorimotor cortical regions than peers 195,196 and that PVI show lower functional connectivity for supplementary motor areas compared to peers 196 when seeding the lesioned M1. Higher intrahemispheric functional connectivity in the anterior supramarginal gyrus in the lesioned hemisphere of AIS was also observed compared to both typically developing peers and PVI.…”
Section: Sensorimotor Networkmentioning
confidence: 99%
“…194 A multimodal study in PVI suggested that differences in inter-and intrahemispheric functional connectivity may be CST-wiring specific. 194 Seed-based analyses have indicated that AISs have significantly lower interhemispheric functional connectivity values in sensorimotor cortical regions than peers 195,196 and that PVI show lower functional connectivity for supplementary motor areas compared to peers 196 when seeding the lesioned M1. Higher intrahemispheric functional connectivity in the anterior supramarginal gyrus in the lesioned hemisphere of AIS was also observed compared to both typically developing peers and PVI.…”
Section: Sensorimotor Networkmentioning
confidence: 99%
“…Moreover, previous study with the network-based statistic (NBS) analysis demonstrated that fractional anisotropy (FA) with basal ganglia (mainly putamen and pallidum) and thalamus were significantly reduced in CP children ( 40 ). Gray matter lesions were also found in the basal ganglia of CP children, mainly located in bilateral putamen ( 46 ). The damaged posterior thalamic radiation connecting the thalamus to the posterior parietal and occipital cortex, was found to be associated with motor dysfunction in children with spastic CP ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Selected studies were assessed for quality and bias with the application of the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) 26 . * Two 31,32 and three studies [27][28]35 recruited from the same database.…”
Section: Study Selectionmentioning
confidence: 99%
“…The 10 studies included in this systematic review comprised 260 individuals with a history of perinatal brain injury (145 [55%] males) and 290 controls (159 [55%] males), with results summarised in Table 2. Of the studies assessing motor outcome, one study assessed whether rs-fMRI at term-equivalent age (TEA) would be predictive of motor impairments at followup at 4 and 8 months of age 29 , and the remaining 6 studies investigated the relationship between rs-fMRI and motor functioning cross-sectionally in individuals between 3 and 19 years of age [27][28][29][30][31][32][33] . 3 studies also assessed the association between rs-fMRI and language performance at the same time-point in individuals between 3 years 6 months and 29 years 1 month [34][35][36] .…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation